Bridging Theory and Community: Enhancing Geomatics Education for Civil Engineers Through a Service Learning Pedagogy (Journal of Asian Geography, 2026)
Modern engineering education faces the critical challenge of preparing graduates for complex, real-world problems that demand not only technical proficiency but also social awareness and professional skills. Service-learning, a pedagogical approach that integrates meaningful community service with academic instruction, presents a high-impact solution. This paper examines the effectiveness of service-learning in a Geomatics course for Civil Engineering students through a case study of the K.A.D.A.I.T.A.N. project at Xavier University - Ateneo de Cagayan. The project addressed the recurring flood vulnerability of Sitio Kadaitan, a community in Alubijid, Misamis Oriental, Philippines. Students applied their Geomatics skills to conduct a comprehensive flood hazard and risk assessment, producing professional-quality outputs such as topographic maps, flood susceptibility maps, science-based solutions, and river easement delineations. This analysis demonstrates that the service-learning model, structured around problem-based learning, mentored experiential learning, and structured reflection, fosters a unique set of learning outcomes. Evidence from the project report reveals that students achieved mastery in technical application, developed higher-order cognitive skills like critical thinking and complex problem-solving, and cultivated key professional competencies aligned with ABET criteria, including teamwork, communication, and ethical responsibility. Furthermore, the project instilled a profound sense of civic engagement and social responsibility. This paper concludes by presenting an actionable framework for integrating service-learning into Geomatics and Civil Engineering curricula, proposing it as a vital pedagogy for developing competent, conscientious, and socially responsible engineers capable of addressing 21st-century challenges.